Modeling Marsh Dynamics Using a 3-D Coupled Wave-Flow-Sediment Model - Kalra, Tarandeep S.; Ganju, Neil K.; Aretxabaleta, Alfredo L.; Carr, Joel A.; Defne, Zafer; Moriarty, Julia M. (Frontiers in Marine Science, 2021)
Salt marshes are dynamic biogeomorphic systems that respond to external physical factors, including tides, sediment transport, and waves and as well as internal processes such as autochthonous soild formation. Predicting the fate of marshes under future storms and sea-level rise requires a modeling framework that accounts for these processes in a coupled fashion. In this study, we implement two new marsh dynamic processes in the 3-D COAWST (coupled-ocean-atmosphere-wave sediment transport) model. The processes included are the erosion of the marsh edge scarp caused by lateral wave thrust from surface waves and vertical accretion driven by organic growth on the marsh platform. The edge erosion in the model occurs due to surface waves that reach grid cells at the marsh boundary; the associated lateral wave thrust lateral wave thrust leads to sediment release from these boundary cells to adjacent open water cells (non-marsh cells). Once a sufficient sediment is lost from a marsh-edge grid cell, the marsh cell is converted to a non-marsh cell, conceptually representing an intertidal mudflat. The sediment released from the marsh causes a change in bathymetry, thereby modifying the wave-energy reaching the marsh face. The vertical accretion occurs due to biomass production and is calculated by fitting a parabolic productivity curve between mean high water (MHW) and maximum vegetation depth for a given tidal range. MHW and tidal range are stored at user-defined intervals (on the order of days) as a hindcast and used to update the vertical growth formulation. Idealized domains are utilized to verify the lateral wave thrust formulation and show the dynamics of lateral wave erosion leading to horizontal retreat of marsh edge. The simulations of Reedy and Dinner Creeks within the Barnegat Bay estuary system show the model capability to account for both lateral wave erosion and vertical accretion due to organic growth in a realistic marsh complex. The simulations show that majority of accretion over the marsh complex occurs due to organic production while most estuarine sediment deposition occurs along the channel edges.